FABRICATION OF MEMS-BASED ELECTROTHERMAL MICROACTUATORS WITH ADDITIVE MANUFACTURING TECHNOLOGIES - YÜCE, HÜSEYİN; AKKUŞ, NİHAT (INST ZA KOVINSKE MATERIALE I IN TEHNOLOGIE, 2019)
This study aimed to fabricate a bidirectional electrothermal microactuator that can be produced with the conventional micro-electromechanical system (MEMS) fabrication technique, using two-photon polymerization (2PP) and projection micro-stereolithography (P mu SL) methods and to compare these methods with each other. The electrothermal microactuator that can move in two directions was designed in accordance with determined criteria. Although the same design was used for the 2PP and P mu SL methods, the supporting structures were not produced with the P mu SL method. For the P mu SL method, the actuator was produced by removing the supports from the original design. Although 2-mu m-diameter supports could be fabricated with the 2PP method, it was not possible to produce them with the P mu SL method. Furthermore, the 2PP method was found to be better than the P mu SL for the production of complex, non-symmetric support structures.
Keywords: MEMS; 2PP; P mu SL; thermal actuator; 3D-printer; 2-PHOTON POLYMERIZATION